Talking Stick dalam Pembelajaran sebagai Upaya Meningkatkan Minat Belajar Siswa pada Pembelajaran Seni Budaya Kelas VII MTs Negeri 3 Bengkulu Utara - ANNY ARIFAH (UIN Fatmawati Sukarno Bengkulu, 2024)
This implementing classroom learning, was used of varied learning models is still very low and teachers tend to use conventional models in every lesson they carry out. This may be due to teachers' lack of mastery of existing learning models, even though mastery of learning models is very necessary to improve teachers' professional abilities. Students today tend to expect their teachers to teach in a more relaxed and exciting way. The talking stick method is an interactive learning method because it emphasizes active student involvement during the learning process. Teachers can carry out learning using various approaches. This research aims to increase student learning activities in environmental education learning. The research method used in this research is classroom action research. The research results obtained from this research are: The application of talking sticks can increase students' learning motivation and active learning in the art and culture learning process, can increase the motivation and active learning of each individual student, and can make students play an active role in learning, and the learning atmosphere becomes more life. with the results of the percentage of students with a good predicate of 31%, medium 42% and low 27% in cycle one. In the second cycle, the percentage of students with good grades was 38%, moderate 40% and low 22%. In the third cycle, the percentage of students with good grades was 70%, moderate 20% and low 9%. So, it can be concluded that there is an increase in the presentation of student interest in each cycle carried out.